Increasing Diversity in Cognitive Developmental Research: Issues and Solutions - Rowley, Stephanie J.; Camacho, Tissyana C. (Journal of cognition and development, 2015)
The current article discusses the importance of increasing racial-ethnic and socioeconomic diversity in cognitive developmental research. It begins with discussion of the implications of the underrepresentation of ethnic minority children in cognitive developmental research. It goes on to suggest reasons underlying these omissions, such as the cost of effective recruitment methods, fear of committing cultural faux pas, and lack of expertise interacting with such populations. Finally, recommendations for addressing such limitations are provided via examples of successful and innovative methodological techniques used in prior research with ethnic minority children.